2023
DOI: 10.3390/su15086697
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of A Procedure to Improve the Extraction Rate of Biologically Active Compounds in Red Grape Must Using High-Power Ultrasound

Abstract: The primary focus in the production of quality red wine is the extraction of grape components, which can be achieved in a variety of ways. This work investigates the extraction yield of biologically active compounds from crushed Merlot grapes, as a result of ultrasound treatment applied before maceration, and optimizes the process parameters of a laboratory scale using response surface methodology (RSM) within a central composite design (CCD) model. The two factors whose response was studied were amplitude (A)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 69 publications
0
1
0
Order By: Relevance
“…Priyanka et al [21] optimized the properties of eco-friendly, self-cleaning concrete containing marble dust and stearic acid using the RSM and found that a partial replacement rate of 30% was optimal for the self-cleaning property. Alina et al [22] used the RSM to optimize the extraction yield of biologically active compounds from crushed Merlot grapes using ultrasound treatment before maceration. Sushrut S. et al [23] optimized fuel flow rates in a DF engine using the RSM for improved brake thermal efficiency and reduced exhaust emissions.…”
Section: Introductionmentioning
confidence: 99%
“…Priyanka et al [21] optimized the properties of eco-friendly, self-cleaning concrete containing marble dust and stearic acid using the RSM and found that a partial replacement rate of 30% was optimal for the self-cleaning property. Alina et al [22] used the RSM to optimize the extraction yield of biologically active compounds from crushed Merlot grapes using ultrasound treatment before maceration. Sushrut S. et al [23] optimized fuel flow rates in a DF engine using the RSM for improved brake thermal efficiency and reduced exhaust emissions.…”
Section: Introductionmentioning
confidence: 99%